Pengaruh Sistem Full Day School Terhadap Motivasi Belajar dan Pembentukan Karakter Siswa di SD Nasima Semarang - Luthfatul Maghfiroh; Jihan Fatma Ayuni; Wanda Putri Anggraini; Auliya Nur Rofikoh; Rakanita Dyah Ayu Kinesti (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the influence of the full day school system on learning motivation and character formation of students at SD Nasima Semarang. The research method used is descriptive quantitative with data collection through questionnaires given to students and teachers. The research results show that the implementation of the full day school system has a positive impact on student learning motivation, which is characterized by increased interest and participation in learning activities. Apart from that, this system also plays a significant role in forming student character, such as discipline, responsibility and cooperation. However, there are several challenges that need to be considered, such as student fatigue and the need for varied teaching methods. In conclusion, the full day school system at SD Nasima Semarang generally has a positive influence on students' learning motivation and character formation, although improvements and adjustments are still needed to optimize the results achieved.